2010
DOI: 10.1121/1.3308469
|View full text |Cite
|
Sign up to set email alerts
|

Whistles emitted by Atlantic spotted dolphins (Stenella frontalis) in southeastern Brazil

Abstract: The whistles of Atlantic spotted dolphins have been studied in a few localities of the North Atlantic Ocean and those studies revealed that the species emits whistles within a broad frequency range, with a high number of inflection points and presence of harmonics. In the South Atlantic Ocean, there is no information about the sounds produced by Atlantic spotted dolphins. A total of 1092 whistles emitted by free-ranging Atlantic spotted dolphins in Southeastern Brazilian coastal waters were analyzed. Whistles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
8
2
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 17 publications
(18 reference statements)
3
8
2
2
Order By: Relevance
“…4). The mean of the BF was significantly higher than the EF; this was inconsistent with the findings observed for other odontocetes (Baz ua-Dur an and Au, 2002;Azevedo et al, 2010).…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…4). The mean of the BF was significantly higher than the EF; this was inconsistent with the findings observed for other odontocetes (Baz ua-Dur an and Au, 2002;Azevedo et al, 2010).…”
Section: Discussioncontrasting
confidence: 55%
“…Whistles with a fundamental frequency higher than 20 kHz (line of demarcation of the ultrasonic frequency), 22 kHz (the upper boundary of the recorder frequency response in Parijs and Corkeron, 2001b,a), and 24 kHz (the upper limit of the recorder frequency response in Seekings et al, 2010, also selected for comparison with other studies) accounted for only 1.3%, 0.8%, and 0.2%, respectively. This rare usage of whistles with a fundamental frequency extending beyond ultrasonic frequency has also been observed in Atlantic spotted dolphins (Stenella frontalis), where whistles above 14 kHz are rare (Azevedo et al, 2010) and in Hawaiian spinner dolphins (Stenella longirostris), where the fundamental MaxF beyond 22 kHz and 24 kHz accounted for less than 5% and 2%, respectively (Baz ua-Dur an and Au, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Azevedo et al, 2010;Díaz López, 2011;Hernandez et al, 2010;May-Collado, 2013). Several whistle types (Lilly, 1963;Rehn, Filatova, Durban, & Foote, 2011) or call combinations incorporating whistles have also been linked to high states of emotional arousal (see Herzing, 2000 for a review).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, although variation in acoustic parameters can relate to behavioural state (Azevedo et al, 2010;MayCollado, 2013) and may be useful in predicting surface behaviour (Henderson, Hildebrand, & Smith, 2011;Henderson, Hildebrand, Smith, & Falcone, 2012;Hernandez, Solangi, & Kuczaj, 2010) the available information poorly explains the causative factors of this variability. Esch, Sayigh, Blum, et al's (2009) study is the notable exception in detailing the influence of stress on whistle parameters and production rates.…”
mentioning
confidence: 99%
“…These results indicate in this study their simple contour (Belikov and Bel'Kovich, 2007;MayCollado et al, 2007). A great amount of constant whistles were frequently emitted, which is not commonly reported for other species of delphinids (Azevedo and Van Sluys, 2005;Ansmann et al, 2007;Azevedo et al, 2010;Hawkins and Gartside, 2010) and has not been previously reported for this species (Evans, 1967;Oswald et al, 2003Oswald et al, , 2007. For rough-toothed dolphins that were recorded while captured at sea in the Central Pacific Ocean, descending whistles were frequently emitted (Evans, 1967), but the whistles recorded in Rio de Janeiro presented small modulations in frequencies throughout the signals, with no abrupt falling frequency patterns.…”
Section: Discussionmentioning
confidence: 96%